A= 1/1.3 + 1/3.5 + 1/5.7 + 1/7.9 + 1/9.11 B= 1/2 + 1/2^2 + 1/2^3 +…+ 1/2^100 21/09/2021 Bởi Quinn A= 1/1.3 + 1/3.5 + 1/5.7 + 1/7.9 + 1/9.11 B= 1/2 + 1/2^2 + 1/2^3 +…+ 1/2^100
Đáp án: `2A=2.( 1/(1.3) + 1/(3.5) + 1/(5.7) + 1/(7.9) + 1/(9.11))` `2A=2/(3.5)+2/(5.7)+2/(7.9)+2/(9.11)` `2A=1/3-1/5+1/5-1/7+1/7-1/9+1/9-1/11` `2A=1/3-1/11=8/33` `A=8/33:2=4/33` Vậy A=`4/33` `B= 1/2 + 1/(2^2)+ 1/(2^3) +…+ 1/(2^100)` `2B=1+1/2+1/(2^2)+….+1/(2^99)` `2B-B=(1+1/2+1/(2^2)+….+1/(2^99))-( 1/2 + 1/(2^2)+ 1/(2^3) +…+ 1/(2^100))` `B=1+1/2+1/(2^2)+………+1/(2^99)-1/2-1/(2^2)-…………….-1/(2^100)` `B=1-1/(2^100)=(2^100-1)/(2^100)` Vậy `B=(2^100-1)/(2^100)` XIN HAY NHẤT NHA Bình luận
2A=2(1/1.3+1/3.5+1/5.7+1/7.9+1/9.11) 2A=2/1.3+2/3.5+2/5.7+2/7.9+1/9.11 2A=1-1/3+1/3-1/5+1/5-1/7+1/7-1/9+1/9-1/11 2A=1-1/11 2A=11-1/11 2A=10/11 A=10/11.1/2 A=5/11 Vậy A=5/11 2B=2( 1/2 + 1/2^2 + 1/2^3 +…+ 1/2^100) 2B=1+1/2 + 1/2^2 + 1/2^3 +…+ 1/2^99 2B-B=( 1/2 + 1/2^2 + 1/2^3 +…+ 1/2^100)-(1+1/2 + 1/2^2 + 1/2^3 +…+ 1/2^99) B=1/2^100-1 B=2^100-1/2^100 Vậy B=2^100-1/2^100 Bình luận
Đáp án:
`2A=2.( 1/(1.3) + 1/(3.5) + 1/(5.7) + 1/(7.9) + 1/(9.11))`
`2A=2/(3.5)+2/(5.7)+2/(7.9)+2/(9.11)`
`2A=1/3-1/5+1/5-1/7+1/7-1/9+1/9-1/11`
`2A=1/3-1/11=8/33`
`A=8/33:2=4/33`
Vậy A=`4/33`
`B= 1/2 + 1/(2^2)+ 1/(2^3) +…+ 1/(2^100)`
`2B=1+1/2+1/(2^2)+….+1/(2^99)`
`2B-B=(1+1/2+1/(2^2)+….+1/(2^99))-( 1/2 + 1/(2^2)+ 1/(2^3) +…+ 1/(2^100))`
`B=1+1/2+1/(2^2)+………+1/(2^99)-1/2-1/(2^2)-…………….-1/(2^100)`
`B=1-1/(2^100)=(2^100-1)/(2^100)`
Vậy `B=(2^100-1)/(2^100)`
XIN HAY NHẤT NHA
2A=2(1/1.3+1/3.5+1/5.7+1/7.9+1/9.11)
2A=2/1.3+2/3.5+2/5.7+2/7.9+1/9.11
2A=1-1/3+1/3-1/5+1/5-1/7+1/7-1/9+1/9-1/11
2A=1-1/11
2A=11-1/11
2A=10/11
A=10/11.1/2
A=5/11
Vậy A=5/11
2B=2( 1/2 + 1/2^2 + 1/2^3 +…+ 1/2^100)
2B=1+1/2 + 1/2^2 + 1/2^3 +…+ 1/2^99
2B-B=( 1/2 + 1/2^2 + 1/2^3 +…+ 1/2^100)-(1+1/2 + 1/2^2 + 1/2^3 +…+ 1/2^99)
B=1/2^100-1
B=2^100-1/2^100
Vậy B=2^100-1/2^100